Early Contributions to the Evolution of the Canadian Scientific Integrity System: Institutional and Governmental Interaction in the Policy Diffusion Process - Schoenherr, Jordan Richard; Williams-Jones, Bryn (Canadian Journal of Higher Education, 2016)
Academic institutions and research funders have in the last decade devoted considerable effort to developing policies to support academic integrity and prevent misconduct. In this study, we consider the extent to which various initiatives of Canadian federal and provincial (Québec) funders have affected the development of institutional research integrity/misconduct (RIM) policies. Examining the creation and modification dates of 32 institutional RIM policies, we find that federal but not provincial initiatives appear to have the greatest impact on the development of RIM policies. Idiosyncrasies in the creation dates, as well as lack of evidence of a systematic pattern in modification dates, suggest a complex system that is often insulated from certain government initiatives. These results lead us to conclude that there should be greater consistency in the development or updating of RIM policies to ensure the appropriate treatment of misconduct and to encourage behaviour that meets the highest standards of research integrity.